2017
DOI: 10.2139/ssrn.3050323
|View full text |Cite
|
Sign up to set email alerts
|

Does the EU ETS Cause Carbon Leakage in European Manufacturing?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, so far only two studies (Dechezleprêtre et al ., ; Naegele and Zaklan, ) are also those testing for direct evidence of carbon leakage; that is, for whether emissions outside the EU increased as a consequence of the EU ETS. In this case, the very small number of works may be explained by the greater empirical challenges that the particular research question entails.…”
Section: Mapping the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, so far only two studies (Dechezleprêtre et al ., ; Naegele and Zaklan, ) are also those testing for direct evidence of carbon leakage; that is, for whether emissions outside the EU increased as a consequence of the EU ETS. In this case, the very small number of works may be explained by the greater empirical challenges that the particular research question entails.…”
Section: Mapping the Literaturementioning
confidence: 99%
“…In the second, estimated effects can refer to participation in the EU ETS, to carbon prices or some other measure of regulatory stringency. Two of the studies employing panel data models (Costantini and Mazzanti, ; Naegele and Zaklan, ) more specifically estimate gravity‐type models stemming from international trade theory.…”
Section: Mapping the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…While Jaffe and others (1995) find relatively little evidence that environmental policy has had an adverse effect on competitiveness, Dechezleprêtre and Sato (2017) confirm this finding but point towards recent evidence that shows that front-runners of ambitious environmental policies can lead to small adverse effects on trade, employment, plant location, and productivity, particularly for pollution and energy-intensive sectors. Aichele and Felbermayr (2012) suggest that the ratification of the Kyoto Protocol has caused carbon leakage, while Naegele and Zaklan (2017) do not find any evidence that the EU ETS has led to any carbon leakage.…”
Section: Viii2667 New Entrants and Closure Rulesmentioning
confidence: 93%
“…However, the few ex-post studies for the EU ETS have so far not revealed any substantial leakage effect, neither via sectoral trade flows (e.g. Naegele and Zaklan 2016), nor through a rise in Foreign Direct Investment, analyzed for Italian MNEs by Borghesi et al (2016) and for German MNEs by Koch and Basse Mama (2016). The study that most closely shares our conceptual emphasis on potential intra-firm shifts of emissions is Dechezleprêtre et al (2015).…”
Section: Introductionmentioning
confidence: 91%